Assessment of undernutrition by composite index of anthropometric failure among under five children in a slum of Kolkata, West Bengal - Lahiri, Surajit; Lahiri, Saibendu Kumar (International Journal Of Community Medicine And Public Health, 2020)
Background: Under-nutrition is a major public health problem in India among under-five children. Composite index of anthropometric failure (CIAF) provides an overall estimate of under-nutrition as a single measure and helps in detection of children with multiple anthropometric failures. Methods: This cross-sectional community-based study was done in Baghbazar slum of north Kolkata to determine the prevalence of under-nutrition among the under-five children and to find out the determinants of under-nutrition assessed by CIAF using multivariate analysis. WHO Z score system and the composite index of anthropometric failure (CIAF) were used to estimate the magnitude of under-nutrition. Results: 41.2% children were diagnosed with anthropometric Failure. CIAF was more in female (43.1%) than male (39.1%). Multivariate analysis shows that low education level of mother, low socio-economic status (class III and below) and overcrowding were significantly associated with CIAF. Conclusions: CIAF gives a better estimate of under-nutrition than the currently used weight for age Z score. The study shows the importance of proper infant and child feeding practices, family planning practices, appropriate maternal care, female literacy, improvement of economic condition, housing standards and proper treatment of illness in prevention of under-nutrition among under-five children.